(untitled) (Caligrama (São Paulo. Online), 2005)
Admitting the connection between semiotics and psychoanalysis as a starting point for this work and taking into account that psycoanalysis owes to art more than art to psychoanalysis, I intend to demonstrate that there are, in Marco Ferreri movies, especifically in "A Comilança", formal and contentlike connections regarding femininity. These conections go towards Lacan's perspective on the subject. Therefore, Marco Ferreri movies not only offer indicatives, with its antropological and cultural aspects, in contemporary society. To such intent, this work focuses on femininity studying the semiose process related to both filmic text and lacanian metapsychology.